Evidence for Ethylene-Vinyl-Alcohol-Copolymer Liquid Embolic Agent as a Monotherapy in Treatment of Endoleaks. Issue 6 (June 2016) - Jamieson, R.W.; Bachoo, P.; Tambyraja, A.L.
Abstract : Objective: Endoleak remains the Achilles heel of endovascular aneurysm repair and the exclusion of Type II endoleaks, in particular, remains challenging. This systematic review presents the evidence for ethylene-vinyl-alcohol-copolymer liquid embolic agent as a monotherapy in the treatment of endoleaks. Methods: A systematic literature search was performed for all studies reporting the use of liquid embolic agent as a sole agent in the treatment of endoleaks. Patient numbers, clinical details (endoleak type, route of delivery) and outcome in terms of survival, technical and clinical success with freedom from endoleak together with follow-up period were examined. Results: Only 12 articles reporting the use of liquid embolic as the sole treatment modality for endoleaks in 174 patients were identified. All but 21 patients had a Type II endoleak. Transarterial embolization was attempted in 73% of patients with 48 patients having direct sac puncture. Technical success was high at 96%, but in patients with adequate imaging, the clinical success rate dropped to 79%. Complications were sparsely reported and follow-up ranged from 0 to 75 months. Conclusions: This review highlights the lack of data regarding the use of liquid embolic agent as a monotherapy with only 4 studies including more than 10 patients. Data from the largest series suggests a learning curve exists and no study reports on cost effectiveness. Technical success does not always translate into clinical success and with the largest series only reporting median 4-month follow-up no claims regarding durability can be made. In problematic Type II endoleaks, however, liquid embolic agent is a welcome addition to the treatment armamentarium.